Correlating Genotype and Phenotype in the Asexual Yeast Candida orthopsilosis Implicates ZCF29 in Sensitivity to Caffeine. Issue 9 (1st September 2019) - de San Vicente, Kontxi Martinez; Schröder, Markus S; Lombardi, Lisa; Iracane, Elise; Butler, Geraldine
Abstract: Candida orthopsilosis is diploid asexual yeast that causes human disease. Most C. orthopsilosis isolates arose from at least four separate hybridizations between related, but not identical, parents. Here, we used population genomics data to correlate genotypic and phenotypic variation in 28 C. orthopsilosis isolates. We used cosine similarity scores to identify 65 variants with potential high-impact (deleterious effects) that correlated with specific phenotypes. Of these, 19 were Single Nucleotide Polymorphisms (SNPs) that changed stop or start codons, or splice sites. One variant resulted in a premature stop codon in both alleles of the gene ZCF29 in C. orthopsilosis isolate 185, which correlated with sensitivity to nystatin and caffeine. We used CRISPR-Cas9 editing to introduce this polymorphism into two resistant C. orthopsilosis isolates. Introducing the stop codon resulted in sensitivity to caffeine and to ketoconazole, but not to nystatin. Our analysis shows that it is possible to associate genomic variants with phenotype in asexual Candida species, but that only a small amount of genomic variation can be easily explored.